Resection of benign side-branch intraductal papillary mucinous neoplasm of the pancreas—is long term follow-up indicated?: A case report and review of the literature. Issue 7 (February 2018) - Fritz, Stefan; Küper-Steffen, Regina; Feilhauer, Katharina; Sommer, Christoph M.; Richter, Götz M.; Hennig, René; Köninger, Jörg
Abstract: Rationale: Intraductal papillary mucinous neoplasms of the pancreas (IPMNs) are benign cystic tumors with a relevant risk of malignant transformation over time. Currently, follow-up after surgical resection of benign IPMNs remains controversial. Patient concerns: This is a case report of a 68-year-old male who underwent pancreatic head resection for a multicystic side-branch IPMN with low-grade epithelial dysplasia in March 2009 at the Katharinenhospital Stuttgart, Germany. Diagnoses: During postoperative follow-up, a new solid, slightly hypodense lesion in the tail of the pancreas measuring 2.4 cm in diameter was diagnosed in July 2016. Preoperative staging revealed no signs of distant metastasis. Intervention: Subsequently, the patient underwent pancreatic tail resection including splenectomy. Histology revealed IPMN-associated adenocarcinoma of the pancreas pT3, pN1 (2/24), M0, R0. Outcomes: Patients with IPMN bare a relatively high overall risk of developing pancreatic cancer. The 5-year incidence has been described to be as high as 6.9%. The current Consensus-Guidelines therefore recommend a structural life-time follow-up. In contrast, in 2015 the American Gastroenterological Association (AGA) explicitly states that follow-up is not recommended for resected benign IPMN. Currently, a general and international consensus is lacking. Lessons: The presented case demonstrates that even more than 5 years following resection of benign IPMN, pancreatic cancer can occur in a separate location of the pancreatic gland. We believe that IPMNs can be considered as indicator lesions for pancreatic cancer. Patients with resected side-branch IPMN should therefore undergo long term follow-up.